The environmental pollutant and carcinogen 3-nitrobenzanthrone induces cytochrome P450 1A1 and NAD(P)H:quinone oxidoreductase in rat lung and kidney, thereby enhancing its own genotoxicity - Stiborová, Marie; Dracínská, Helena; Mizerovská, Jana; Frei, Eva; Schmeiser, Heinz H; Hudecek, Jirí; Hodek, Petr; Phillips, David H; Arlt, Volker M (Toxicology, 2008)
3-Nitrobenzanthrone (3-NBA) is a carcinogen occurring in diesel exhaust and air pollution. Using the (32)P-postlabelling method, we found that 3-NBA and its human metabolite, 3-aminobenzanthrone (3-ABA), are activated to species forming DNA adducts by cytosols and/or microsomes isolated from rat lung, the target organ for 3-NBA carcinogenicity, and kidney. Each compound generated identical five DNA adducts. We have demonstrated the importance of pulmonary and renal NAD(P)H:quinone oxidoreductase (NQO1) to reduce 3-NBA to species that are further activated by N,O-acetyltransferases and sulfotransferases. Cytochrome P450 (CYP) 1A1 is the essential enzyme for oxidative activation of 3-ABA in microsomes of both organs, while cyclooxygenase plays a minor role. 3-NBA was also investigated for its ability to induce NQO1 and CYP1A1 in lungs and kidneys, and for the influence of such induction on DNA adduct formation by 3-NBA and 3-ABA. When cytosols from rats treated i.p. with 40mg/kg bw of 3-NBA were incubated with 3-NBA, DNA adduct formation was up to 2.1-fold higher than in incubations with cytosols from control animals. This increase corresponded to an increase in protein level and enzymatic activity of NQO1. Incubations of 3-ABA with microsomes of 3-NBA-treated rats led to up to a fivefold increase in DNA adduct formation relative to controls. The stimulation of DNA adduct formation correlated with the potential of 3-NBA to induce protein expression and activity of CYP1A1. These results demonstrate that 3-NBA is capable to induce NQO1 and CYP1A1 in lungs and kidney of rats thereby enhancing its own genotoxic and carcinogenic potential.
Keywords: Environmental Pollutants; karcinogeny; látky znečišťující životní prostředí; mutageny; Microsomes, Liver; Mutagenicity Tests; Rats; Male; benz(a)anthraceny; enzymová indukce; testy genotoxicity; DNA Adducts; NAD(P)H Dehydrogenase (Quinone); Rats, Wistar; mužské pohlaví; NAD(P)H dehydrogenasa (chinon); cytochrom P-450 CYP1A1; Mutagens; krysa rodu Rattus; Enzyme Induction; Cytosol; zvířata; plíce; cytosol; Carcinogens; ledviny; jaterní mikrozomy; Benz(a)Anthracenes; radioizotopy fosforu; potkani Wistar; Kidney; adukty DNA; Phosphorus Radioisotopes; Lung; Cytochrome P-450 CYP1A1; Animals